EVALUATION OF THE EFFECTS OF MAGNETIC FIELDS ON THE GROWTH AND DEVELOPMENT OF BITTER GOURD (Momordica charantia) - Trung Duc, Vu; Duc Ha, Chu; Thi Thanh Nga, Nguyen; Huy Gioi, Dong; Thi Ngoc Quynh, Le; Thi Thanh Huyen, Tran (HNUE Journal of Science: Journal of Natural Sciences, 2025)
Bitter gourd (Momordica charantia), a nutritionally and medicinally important crop, is widely cultivated but faces challenges such as inconsistent yields and environmental stress. Magnetic fields (MFs) have emerged as a promising, non-invasive approach to enhance plant growth and development by influencing key physiological processes. This study evaluated the effects of a 150 mT MF on bitter gourd growth during germination, vegetative emergence, the cotyledon stage, and V1 - V5 vegetative stages by measuring germination rate, germination index, plant height, root length, fresh weight of roots and shoots, chlorophyll content, and leaf area. Results showed that MF-treated seeds achieved a 100% germination rate at 84 hours, compared to 90.25% in the control group, with a consistently higher germination index. During vegetative stages, particularly from V1 to V5, MF-treated plants exhibited slight increases in plant height, root length, and biomass; however, most of these improvements were not statistically significant. These findings suggest that while exposure to a 150 mT MF can significantly improve early-stage germination in bitter gourd, its impact on later vegetative development remains limited and warrants further investigation and optimization. This study builds upon a growing body of research demonstrating the potential of MFs to enhance crop traits, such as germination rate, root elongation, biomass accumulation, and stress tolerance in crops. The results provide a species-specific foundation for advancing the application of MF technology in precision agriculture and crop improvement strategies.